Heat input calculation in GTAW welding to obtain values according to pWPS - Irawan, Benny Haddli; Syahidah, Bilqiz Bazilah; Gemala, Mega (Politeknik Negeri Lhokseumawe, 2025)
This study aims to determine the ideal heat input to remain within the constraints set in the preliminary Welding Procedure Specification (pWPS). Heat input greatly influences weld quality, mechanical properties, and residual stresses, yet accurate determination during Procedure Qualification Record (PQR) trials remains challenging. This research involved field data collection during PQR testing using two coupon specimens made of ASTM B564 UNS-N06625 and ASTM B444 UNS-N06625 Grade 1 materials, each with dimensions of 11.07 mm in thickness and 60.3 mm in diameter. The Gas Tungsten Arc Welding (GTAW) process was applied in the 6G position. The acceptable heat input ranges in the pWPS are: Root (1.0–2.5 kJ/mm), Hot (1.0–2.6), Filler (0.69–1.39), and Cap (0.6–1.1). In coupon test 1, two passes failed: Pass 3 (1.51) and Pass 5 (1.43). In coupon test 2, three passes exceeded limits: Pass 4 (1.64–1.97), Pass 5 (1.42–1.72), and Pass 8 (1.19). To ensure compliance, recommended heat input parameters were formulated. For the root pass, use 97–103 A, 9–10 V, over 4 min 40 sec (2.04–2.41 kJ/mm). For the hot pass, use 98–106 A, 9–10 V, for 4 min 48 sec (1.85–2.23). The filler pass should use 79–97 A, 9–10 V, for 3 min 39 sec (1.01–1.37), and the cap pass 81–90 A, 9–10 V, for 3 min 17 sec (0.64–0.79). These parameters aim to achieve high-quality welds in line with pWPS specifications.